POROSITY AND PATHWAY DETERMINATION IN CRYSTALLINE ROCK BY POSITRON EMISSION TOMOGRAPHY AND NEUTRON RADIOGRAPHY - Pleinert H.; Maguire P.; Lehman E.; Missimer J.; Hammer J.; Leenders K.; Degueldre C.; Bock H.; Townsend D. (My University, 1996)
This study demonstrates that positron emission tomography (PET) and neutron radiography (NR) techniques are complementary methods for determining the fluid pathway and porosity in crystalline rock. After preliminary injection of an organic solvent (e.g. isopropanol) front followed by the injection of the polymer solution (e.g. epoxy used for both techniques) and resin hardening, rock cutting may be performed. Flow pathway may be imaged by using a β+ emitter (e.g.68 Ga) in the resin. With a high-resolution PET camera, determination of the original water carrier features is possible in granodiorite pieces 20 cm in size and in simulated features with porosities of the order of 0.2. The use of a β+ tracer and the camera field, however, limit the lateral resolution of the technique (10 mm). Neutron radiography makes it possible to visualize the simulated porous phases by neutron transmission. The transmission process depends on the neutron scattering properties of the hydrogen-rich material (e.g. epoxy resin). Combination of 2D pictures may rebuild the 3D pattern. Lateral resolution may be in the range of 1 mm; however, the thickness of the rock sample must not exceed 10 cm. Complementarity of these techniques is discussed and they are compared with other methods used to determine porosity.
Keywords: POROSITY; CRYSTALLINE ROCKS; TOMOGRAPHY; NEUTRON METHODS